Pendap as a Bengkulu Culinary Treasure - Nasfati Iktarastiwi; Marwanti Marwanti (Mudra Jurnal Seni Budaya, 2023)
Pendap is a fish-based food that is cooked for 8 hours. Currently, Pendap is one of the culinary heritages of the Bengkulu region. However, of the Pendap is still rarely studied. This study aims to determine Pendap as a culinary treasure typical of Bengkulu. This study uses a qualitative research design with research subjects are pendap producers and owners of typical Bengkulu restaurants, and data collection using observation, interviews, and documentation techniques. Data analysis used an interactive analysis model consisting of data collection and conclusion. The results show that Pendap has existed since 1 century ago and is passed down from generation to generation and is often presented in community events. Pendap has a uniqueness that can be seen from the cooking process which is carried out for 8 hours and has become part of Bengkulu cuisine. Pendap is successfully traded as a Bengkulu typical side dish because it can last for 2 days without preservatives and for 2 weeks if packaged using a vacuum. The results of this study are expected to increase the understanding of people who are involved in the Bengkulu traditional culinary world to pay more attention and know about local wisdom because there are still few studies that discuss the related topics.